Effect of Fire Clay Powder on The Properties of Ceramic Materials Produced by Using Kaolin - Falih, Hazim (Anbar Journal of Engineering Sciences, 2010)
Fire clay are directly into kaolin with different weight percent. Density, shrinkage , water adsorption properties were studies at )1000C0 (and )1200C0 ( . All samples pressed under (10 tan) . The results showed that the fire clay increase density , at the same time decrease the shrinkage and water adsorption .